Produção de ésteres de álcoois da usina sucroalcooleira: caminho para a biorrefinaria - Bellei, João Marcos (Universidade Federal de São Carlos, 2025)
Climate change is one of the greatest challenges facing humanity in the 21st century and could have catastrophic consequences. As a result, an energy transition to replace fossil fuels is urgently needed. Alternatives include biofuels, fuels produced from organic matter. This has led to the emergence of the concept of biorefineries, which consist of industries that seek to produce a range of different products using biomass as a raw material. In recent years, biorefineries have experienced a huge market expansion, so the bioeconomy has great potential for the future. In Brazil, one of the most prominent bioeconomic sectors is the sugar and alcohol industry, which uses sugarcane as a raw material and ethanol as one of its main products. Alcohols, through esterification reactions with carboxylic acids, can generate esters, including ethyl acetate and amyl acetate. These compounds have several applications, especially as solvents and industrial flavorings. Therefore, this study sought to investigate the feasibility of producing ethyl acetate and amyl acetate esters in a sugar and alcohol plant, in order to increase the products synthesized by these industries and direct them to become a multifunctional biorefinery. To this end, process simulations of a multifunctional plant and alternative plants were performed using the free software COCO Simulator, in order to evaluate the reaction and separation configurations. The results demonstrated better conversions using PBR reactors, major limitations in the separation process with conventional unit operations due to the presence of azeotrope, in addition to restrictions of the simulation tool used. Thus, it was concluded that the separation and purification stage constitutes the main obstacle to the ester production process in a plant, so that new studies with more in-depth simulations using more robust software are suggested.
Production of alcohol esters by the sugar and ethanol plant: the path to biorefinery
Keywords: Acetato de amila; Acetato de etila; Biorrefinaria; COCO Simulator; Mudanças climáticas; Simulação; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA